The literary canon in the publishing apparatus - Jipa, Dragos (Primerjalna književnost, 2012)
This essay shows how publishing mechanisms can influence literary discourse in its most critical part, the literary canon. The example of the book series "Les Grands Ecrivains Français" (1887-1913) illustrates how publishing practices such as serialization, material features such as format and the frontispiece, and functions such as that of a series editor contribute to the construction of a literary canon in ways that can be essential to its meaning.
Keywords: založništvo; 19.st.; France; Francija; knjižne zbirke; francoski pisatelji; literarni kanon